- What should be subtracted from a³ -4a² + 5a - 6 to obtain a² - 2a + 1 ?
NO SPAMS
Answers
Answered by
1
Answer:
X = a^3 - 5a^2 + 7a - 7
should be subtracted
Step-by-step explanation:
(a^3-4a^2+5a-6) - X = (a^2-2a+1)
a^3-4a^2+5a-6-(a^2-2a+1) = X
a^3-4a^2-a^2+5a+2a-6-1 =X
Therefore, X = a^3 - 5a^2 + 7a - 7
is the required equation.
Answered by
1
Step-by-step explanation:
here is your answer
have a nice day
Attachments:
![](https://hi-static.z-dn.net/files/d68/49c6146e01c7283ca1c475df182c307b.jpg)
Similar questions
Math,
1 month ago
Environmental Sciences,
1 month ago
Environmental Sciences,
3 months ago
English,
3 months ago
Hindi,
11 months ago
Math,
11 months ago